Business research methods - Blumberg, Boris; Cooper, Donald R.; Schindler, Pamela S. (London : McGraw-Hill Education, 2014)
Designed to lead readers through the research process from start to finish, this text is divided into three thematic areas covering the essentials of research, different types of research, and the best ways of conducting research.
Previous edition: 2011.
Includes bibliographical references and index.
Keywords: Business -- Research -- Methodology; Business and Management